Numerical evaluation of periodic transverse vibration of elastic connecting rods in a six-link mechanism - Nguyen Van Khang; Vu Van Khiem (Vietnam Journal of Mechanics)
Application of the substructure method and d'Alembert's principle to deriving the differential equation of motion of a six-link mechanism with two elastic connecting rods is presented.